2018
DOI: 10.1371/journal.pone.0208884
|View full text |Cite
|
Sign up to set email alerts
|

Closure of live bird markets leads to the spread of H7N9 influenza in China

Abstract: Following the emergence of H7N9 influenza in March 2013, local animal and public health authorities in China have been closing live bird markets as a measure to try to control the H7N9 influenza epidemic. The role of live bird market (LBM) closure on the spread of N7N9 influenza following the closure of LBMs during March to May 2013 (the first wave) and October 2013 to March 2014 (the second wave) is described in this paper. Different provinces implemented closure actions at different times, and intensive medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Another reason could be price changes in neighbouring provinces, which may have provided incentives for traders to collect pigs from more distant counties. A study on live poultry movement in China reported that when the price of poultry changed in neighbouring provinces, the direction of movement of live poultry also changed accordingly (Li et al, ). It is worth noting that the increased supply counties in this network resulted in a change in the structure of the local market trade network.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be price changes in neighbouring provinces, which may have provided incentives for traders to collect pigs from more distant counties. A study on live poultry movement in China reported that when the price of poultry changed in neighbouring provinces, the direction of movement of live poultry also changed accordingly (Li et al, ). It is worth noting that the increased supply counties in this network resulted in a change in the structure of the local market trade network.…”
Section: Discussionmentioning
confidence: 99%
“…Closing LBMs appears to be an effective approach for eradicating or reducing H7N9 infections in humans 32 . However, a recent study presented www.nature.com/scientificreports www.nature.com/scientificreports/ evidence that the closure of LBMs in early waves of H7N9 influenza had resulted in expansion of H7N9 infection to uninfected areas 20 . This implies closing LBMs is a long-term strategy that needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may not be favorable to poultry enterprises or individual households due to the associated financial costs. Reactive closure of LBMs may facilitate further dissemination through the opening of unregistered LBMs or illegal poultry movements 20 .…”
mentioning
confidence: 99%
“…Closing LBMs appears to be an effective approach for eradicating or reducing H7N9 infections in humans [214]. However, a recent study presented evidence that the closure of LBMs in early waves of H7N9 influenza had resulted in expansion of H7N9 infection to uninfected areas [295]. This implies closing LBMs is a long-term strategy that needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may not be favorable to poultry enterprises or individual households due to the associated financial costs. Reactive closure of LBMs may facilitate further dissemination through the opening of unregistered LBMs or illegal poultry movements [295].…”
Section: Introductionmentioning
confidence: 99%